Si-Bookie: flip book berbantuan Augmented Reality guna meningkatkan kemampuan Komunikasi Siswa TK Pangudi Luhur Kartini Semarang - Monika Evanya Kade; Rinanta Dewi; Diva Ari Pradana; Nabilah Dian Avie Anala; Anggita Aura Pinasti; Muhammad Sam’an (Universitas Muhammadiyah Semarang, 2024)
The PKM-PM Si-Bookie program at TK Pangudi Luhur Kartini Semarang aims to enhance children's communication skills through interactive Augmented Reality (AR) and Virtual Reality (VR) technology. The activities began with surveys and problem identification, coordination with the school, program development, as well as teacher socialization and training. The results showed a significant improvement in students' communication abilities; before the program, only 23 out of 33 students dared to speak in front of the class, whereas after the program, this number increased to 30 out of 33 students. Learning enthusiasm and student engagement also increased, with students becoming more excited about using AR and VR technology. Students' confidence in social interactions rose from 23 to 30 students feeling confident after the program. The program also enhanced teachers' technological skills; before the program, only 1 out of 6 teachers understood AR and VR, whereas after the program, 5 out of 6 teachers mastered it. The effectiveness of teaching also improved, with the number of teachers feeling effective rising from 2 to 5. Overall, Si-Bookie successfully improved communication skills and technological abilities at TK Pangudi Luhur Kartini, providing sustainable benefits in education and the community.